The Contribution of Islamic Religious Education Empowered Teachers in Enhancing Students' Academic and Character Development Through Islamic Education - Rahmatilla, Tari; Nasrullah, Yufi Mohammad; Usman, Asep Tutun; Nazib, Fiqra Muhamad (Abjadia : International Journal of Education, 2025)
This study aims to analyze the contribution of the Islamic Religious Education Empowered Teachers in improving students' learning abilities at SMP Negeri 1 Garut, Indonesia. Using a phenomenological qualitative approach, data were collected through in-depth interviews with one Islamic Religious Education teacher and five students. The findings of the study show that the teacher plays an important role in creating a religious and supportive school environment through various spiritual programs, such as Dhuha prayers, routine Qur'an recitation, and congregational Zuhur prayers. Additionally, the teacher introduced an innovative environmental initiative, the "school waste collection movement," which encourages students to bring home at least one piece of trash every day to foster a sense of responsibility for environmental cleanliness. The teaching strategy applied reflects a holistic approach that assesses students' knowledge, attitudes, and skills, while also involving collaboration with other Islamic Religious Education teachers and the wider school community. Despite facing internal challenges, such as maintaining motivation and emotional stability, as well as external challenges such as low learning motivation and limited basic skills among students, the teacher is able to overcome these obstacles through reflective, empathetic, and collaborative approaches. This study concludes that the teacher's diverse contributions not only improve the quality of Islamic Religious Education learning but also support the overall development of students, demonstrating that religious education can have a broader impact on character development and environmental awareness.